Constitutional Procedural Law: A Problematic Concept - García Belaúnde, Domingo (2004)
Constitutional Procedural Law is a discipline that has evolved and gained legitimacy over time. However, there are still questions surrounding this branch of law. The definition of its meaning still represents a challenge for the doctrine. In this sense, the aim of this paper is to explore the origin of the concept and to offer an adequate definition. To this end, the author analyses recent developments and advances in the field. Although important points are addressed, there are still relevant questions that need to be explored in order to achieve a more complete understanding of this discipline.